Uma Abordagem em Espiral para Disciplinas Iniciais de Programação na Educação Profissional em Informática - Araujo, Luis Gustavo de Jesus (2018)
Teaching programming is a great challenge in every educational stage and in several institutions of the world, being a general problem in the area of computing education. In the Brazilian Informatics vocational high school programs, historical issues of the Professional Education System in Brazil make this problem even harder. With these issues in mind, we proposed and evaluated a teaching approach based on spiral learning associated with programming environments for novices and contexts relevant to students, aiming to improve motivation and learning in programming courses. Three case studies were carried out: one in Midlle School, and two in vocational high school programs in Informatics in Feira de Santana, Bahia, Brazil. The case studies were split into three contextualized blocks, where programming content was learned through a context, using appropriate tools. Contexts such as games, geometric figures and images were used, as well as Scratch, JES and PPlay tools. Given the qualitative and quantitative nature of this research, we used sur- veys, interviews, observations, evaluations and logbooks to obtain the data. Results on motivation are described in terms of the ARCS model (Attention, Relevance, Confidence and Satisfaction), and the results on learning are described from student exams and qualitative data. Results point to high levels of motivation during the whole approach and to the influence in student motivation of either maintaining or changing context and tools used in each block. Regarding learning, results demonstrate that the approach has enhanced learning of some concepts. One noti- ces that Scratch helped in understanding Functions, Select and Repeart Structures, and that the use of the Python language led to better understanding of Variables and Relational Operators. About object-oriented programming concepts, students showed ease with Classes, Constructors, Objects and Variables. This study also reveals the mutual influence between student motivation and learning. The results, materials, research design and the courses presented in this work may contribute to the design of other vocational courses and to the research on teaching and learning programming.